Traditional application and modern pharmacological research of Eucommia ulmoides Oliv. - Lichuang Huang; Qiang Lyu; Wanying Zheng; Qiao Yang; Gang Cao (BMC, 2021)
Abstract As a Traditional Chinese Medicine, Eucommia ulmoides Oliv. has been used for the treatment of various diseases since ancient times, involving lumbar pain, knee pain, osteoporosis, hepatoprotection, paralysis, intestinal haemorrhoids, vaginal bleeding, abortion, spermatorrhoea, foot fungus, anti-aging etc. With the developing discovery of E. ulmoides extracts and its active components in various pharmacological activities, E. ulmoides has gained more and more attention. Up to now, E. ulmoides has been revealed to show remarkable therapeutic effects on hypertension, hyperglycemia, diabetes, obesity, osteoporosis, Parkinson's disease, Alzheimer's disease, sexual dysfunction. E. ulmoides has also been reported to possess antioxidant, anti-inflammatory, neuroprotective, anti-fatigue, anti-aging, anti-cancer and immunoregulation activities etc. Along these lines, this review summarizes the traditional application and modern pharmacological research of E. ulmoides, providing novel insights of E. ulmoides in the treatment of various diseases.